2017
DOI: 10.1016/j.microrel.2017.07.059
|View full text |Cite
|
Sign up to set email alerts
|

Capacitive effects in IGBTs limiting their reliability under short circuit

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognize and abide by the legal requirements associated with these rights.  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…In [14], it has been pointed out for the first time that a parametric oscillation takes place during the IGBT short circuit, whose time-varying element is the Miller capacitance, leading to the amplification mechanism. This occurs when the electric field at the emitter side of the IGBT becomes too weak, as a consequence of the electric field rotation.…”
Section: A Short-circuit Optimized Igbt Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In [14], it has been pointed out for the first time that a parametric oscillation takes place during the IGBT short circuit, whose time-varying element is the Miller capacitance, leading to the amplification mechanism. This occurs when the electric field at the emitter side of the IGBT becomes too weak, as a consequence of the electric field rotation.…”
Section: A Short-circuit Optimized Igbt Designmentioning
confidence: 99%
“…2), The Kirk Effect in IGBTs is related with the root cause of such high-frequency oscillations. In [14], it has also been found that such oscillation phenomenon can be recognized as a parametric oscillation, whose time-varying element is the Miller capacitance. In [14], it has been demonstrated that it is possible to relate the electric field distortions to gate capacitance variations, and associate the capacitance variation with charge-storage effects, occurring at the surface of the IGBT.…”
Section: Introductionmentioning
confidence: 99%
“…Insulate gate bipolar transistor (IGBT) is the key component in the power system, which could be used in a range of several hundred volts to several thousand volts. Power devices are considered as the most fragile components in the power system, and will experience extreme conditions during the long-term wear-out [1,2]. Therefore, monitoring and predicting failure are always carried out to effectively improve reliability and prolong the life span of IGBTs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, blanking time is needed to avoid false triggering. M. Chen group proposed a self-adaptive blanking circuit for IGBT short-circuit protection based 1 on VCE monitoring where a fixed delay time unit still exists to cope with the hard switching failure [24,25]. This paper introduces an improved self-adaptive blanking time circuit.…”
Section: Introductionmentioning
confidence: 99%